IoT System for Real-Time Water Quality Measurement and Data Visualization - Koleva, Radmila; Zaev, Emil; Babunski, Darko; Rath, Gerhard; Ninevski, Dimitar (IEEE, 2023)
A prototype of a cheap IoT system for real-time monitoring of river water quality has been developed. The system consists of monitoring stations and appropriate presentation devices (computer, phone, or similar). Each monitoring station has a possibility for real-time measurement of 4 parameters: temperature, pH, turbidity, and dissolved oxygen. They are measured through probes submerged directly in the water. The probes are connected to the Raspberry Pi 3 model B, and through wi-fi communication, the measured data are transferred to the data storage cloud and then transferred to the visualization platform. The collected data in the IoT system is calculated and presented in real-time. Using real-time we can have instant information on the water quality and an alarm for possible contamination. Collected data on the remote server station can be used for deeper water quality analysis.
Keywords: monitoring water quality; IoT measurement; Real-time data analytics; Cloud computing; IoT Health care system